Bioavailability of zinc from different organic zinc chelates and their effect on the growth, whole body, tissue zinc content, enzymes activity and proximate composition of L. rohita. - Muhammad Tahir; Noor Khan; Mahroze Fatima; Naveed Ul Haque; Simon J Davies (PLoS ONE)
Minerals play an essential role in aquatic animals to maintain their normal physiological and metabolic functions. This feeding trial assessed the impact of various zinc sources on L. rohita performance. Dietary treatments included a Control group with zinc sulfate (226.25 mg/kg), and treatment groups with zinc citrate (150.15 mg/kg), zinc acetate (230.56 mg/kg), zinc monomethionine (244.75 mg/kg), and zinc gluconate (395.94 mg/kg). In 15 aquaria, 300 fish (15.84 ± 0.07g) were randomly distributed in triplicate groups. Results revealed significantly (P < 0.05) higher final body weight (FBW), feed conversion ratio (FCR), body weight gain (BWG), and sediment growth rate (SGR) for zinc gluconate fed fish compared to the other sources. Zinc gluconate fed L. rohita also exhibited the lowest feed intake, while initial body weight (IBW) and survival rate (SR %) did not significantly differ. Proximate fish analysis showed non-significant (P > 0.05) differences among treatments. Tissue zinc analysis demonstrated significantly (P < 0.05) higher zinc content in L. rohita receiving zinc gluconate. Antioxidant enzyme activity indicated lower (2.12 ± 0.01) thiobarbituric acid reactive substances (TBARS) in the zinc gluconate treatment, with elevated levels of key biomarker enzymes, glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase (SOD). Stress and immune response indicators revealed significantly lower hematocrit (HCT), cortisol (CRT), and glucose (GLU) levels in zinc gluconate fed fish, while CRT was higher (36.62 ± 0.65 mg/ml). Blood serum parameters, including alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP), remained lower (29.65 ± 0.85 U/ml, 84.76 ± 2.45 U/ml, and 212.87 ± 6.14 U/ml), in fish fed zinc gluconate respectively. In conclusion, different organic zinc sources, particularly zinc gluconate, improved L. rohita growth, tissue zinc concentration, antioxidant enzyme activity, blood serum parameters, and stress and immune response to varying extents.